Observational Study of Pedestrian Behavior at Signalized Crosswalks - Damian Frej (Communications)
The pedestrian behavior at five signalized crosswalks in Kielce, was analyzed in this study with a particular focus on the increasing use of mobile phones and other electronic devices while crossing the street. Compared to previous ITS studies, which showed that 7% of pedestrians used phones, the current study reveals a significant increase in this phenomenon, with percentages ranging from 14 to 60%. The highest levels of phone usage and risky behaviors were observed at the intersection of Aleja Solidarnosci and Swietokrzyska Street. The results also indicate a decrease in the number of cases of crossing on a red light but an increase in the number of pedestrians crossing during the flashing green signal. The study results point to the need for targeted educational campaigns and the adaptation of infrastructure to address the new challenges associated with mobile device use by pedestrians.